Development and usability of a novel holographic 3-dimensional user interface using hand-gesture control for a future vehicle application by older adults. (September 2018) - Schwambach, Breno; Brooks, Johnell; Venhovens, Paul; Knizek, Robert; Mims, Lauren; Jenkins, Casey; McConomy, Shayne; Yang, Yang; Karg, Jochen; Weber, Julian; Schulte, Joerg
The Deep Orange program immerses automotive engineering students into the world of an OEM as part of their graduate education. While developing the program's seventh vehicle concept, students explored new human machine interface concepts with the goal of having a clean, minimal interior design. One outcome of their ideation process is a concept for a holographic companion that can act as a concierge for all functions of the vehicle. After creating a prototype of the holographic display using existing technologies and developing a user interface controlled by hand gestures, a usability study was performed with older adults. The results suggest the system was not intuitive. Participants demonstrated better performance with tasks using discrete hand motions in comparison to those that required continuous motions. The data were helpful to understand the challenges of untrained users interacting with a new HMI system.